2017
DOI: 10.1038/s41598-017-05621-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Pseudomonas aeruginosa mutational resistome in an international Cystic Fibrosis clone

Abstract: Emergence of epidemic clones and antibiotic resistance development compromises the management of Pseudomonas aeruginosa cystic fibrosis (CF) chronic respiratory infections. Whole genome sequencing (WGS) was used to decipher the phylogeny, interpatient dissemination, WGS mutator genotypes (mutome) and resistome of a widespread clone (CC274), in isolates from two highly-distant countries, Australia and Spain, covering an 18-year period. The coexistence of two divergent CC274 clonal lineages was revealed, but wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
178
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(191 citation statements)
references
References 65 publications
10
178
1
2
Order By: Relevance
“…To examine if the precise mutations found in our in vitro study were also found in clinical isolates, we searched published genomes of P. aeruginosa clinical isolates from cystic fibrosis patients who had likely been treated with aminoglycosides like TOB (Bolard et al, 2017; Chung et al, 2012; López-Causapé et al, 2017, 2018; Markussen et al, 2014). We identified fusA1 and ptsP mutations in these genomes, suggesting that these mutations evolve during infections.…”
Section: Resultsmentioning
confidence: 99%
“…To examine if the precise mutations found in our in vitro study were also found in clinical isolates, we searched published genomes of P. aeruginosa clinical isolates from cystic fibrosis patients who had likely been treated with aminoglycosides like TOB (Bolard et al, 2017; Chung et al, 2012; López-Causapé et al, 2017, 2018; Markussen et al, 2014). We identified fusA1 and ptsP mutations in these genomes, suggesting that these mutations evolve during infections.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in contrast to the 1995 isolate, the 2002 and all the 2011 isolates showed susceptibility to piperacillin-tazobactam, resistance to which seems to have been lost after the acquisition of resistance to tobramycin, thus suggesting collateral sensitivity to penicillin-type-β-lactams as previously described by Barbosa et al (29). On the other hand, even though colistin was used from 2004, all isolates showed MIC values ranging from 8 to 32 µg/ml, which are relatively high compared to other data sets from clinical isolates (27, 28, 30, 31) (Fig. 2).…”
Section: Resultsmentioning
confidence: 68%
“…In order to investigate the molecular bases of the antimicrobial resistance observed in CFD isolates, we explored the acquisition of mutations in a set of 168 chromosomal genes, here defined as the resistome, which have been described to be involved in P. aeruginosa antibiotic resistance mechanisms (27, 28, 32). Thus, using the 1991 genome as reference, we analyzed the distribution of a total of 5710 SNPs and 1078 indels accumulated in a period of 20 years of infection, which we have previously detected in the collection of isolates by WGS analysis (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have confirmed the involvement of genes previously proposed to be associated with resistance in P. aeruginosa. These include the fusA1 gene that encodes the EFG-1 protein and is associated with aminoglycoside resistance (27,29,30) and the ftsI gene that encodes a penicillin binding protein and is associated with carbapenem resistance (30)(31)(32)(33)(34). This approach has high potential for identifying previously unknown antibiotic resistanceassociated mutations and genes, but some key issues remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%